Examining Second Language Listening, Vocabulary, and Executive Functioning - Wallace, Matthew P.; Lee, Kerry (Frontiers in Psychology, 2020)
Performance on second language (L2) listening tests is influenced by individual differences in listener characteristics (e.g., executive functioning and vocabulary size) and characteristics of the listening measure (e.g., text length or skills measured). For listeners, the amount of linguistic knowledge is most important for comprehension outcomes. As language proficiency increases, non-linguistic factors, like the executive functions (EF) of working memory, purportedly begin to exert influence on listening performance. EF represents the range of functions performed by the central executive (the processing component) of the working memory system and have largely been studied in the context of updating (revising information held in temporary storage) and shifting (switching attentional focus among mental representations). To test these theoretical claims, the relationship among L2 listening, vocabulary size, updating, and shifting was examined. This included a moderation analysis to investigate whether the relationship between EF and listening was dependent upon vocabulary size. The relationships among the variables were also examined for varied test characteristics to see if contributions from EF and vocabulary differed according to text length or skill measured. In total, 209 Japanese senior high school EFL learners completed a standardized listening test and tests measuring updating, shifting, and vocabulary size. Results from structural equation modeling showed that only vocabulary was predictive of listening performance, regardless of text length or skill measured on the test. Results also showed that vocabulary size did not moderate the relationship between EF and listening, suggesting that the non-linguistic factors were not important for listening regardless of vocabulary size. The findings support claims that linguistic knowledge is most important for listening and that non-linguistic factors are less important for low-level listeners. The findings also contribute empirical evidence for the relationship between L2 listening and EF, a novel conceptualization of the working memory construct.